(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The research aimed to identify the impact of employing modern technologies on the effectiveness of performance monitoring within the framework of strategic planning. This was done through an applied study conducted in the Salah al-Din Governorate Education Directorate, which served as the field of research. The research relied on a descriptive analytical approach, and its sample consisted of (132) individuals working in the field of modern technology across the various departments affiliated with the directorate. Data and information were collected from the sample members using a questionnaire (the research scale). After distribution and retrieval, two questionnaires were found to be unsuitable for analysis. The collected data and information were analyzed using the statistical program (SPSS v.25). The study yielded several final results, the most notable of which were: the existence of a statistically significant correlation and influence between the two research variables (the employment of modern technologies and the effectiveness of performance monitoring). The research also concluded with a number of recommendations, the most important of which was the need to enhance the adoption of modern technologies, especially artificial intelligence applications, given their clear positive impact on improving the performance of the organization under study.